Nadsat in translation: A Clockwork Orange and L’Orange Mécanique - Vincent, Benet; Clarke, Jim (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2020)
Anthony Burgess’s 1962 novella A Clockwork Orange is one of the most popular speculative works of fiction of all time, having been translated over fifty times into more than thirty different languages. Each translator of this work is faced with the challenge of adapting Burgess’s invented anti-language, Nadsat, into their target language. Some translations have managed this more successfully than others. The French translation, by Georges Belmont and Hortense Chabrier, L’Orange Mécanique (1962/1972) is considered particularly successful and remains the standard French translation nearly 50 years on. Previous studies have remarked on the creativity shown by these translators in reconstructing Nadsat in the target language. However, previous work has not closely analysed the consistency that Belmont and Chabrier brought to this task. In this paper, we use corpus linguistics methodologies to examine the construction of French-Nadsat, and compare it to the Nadsat presented in the source text. We identify six categories of French-Nadsat, all of which are in some way analogous with categories identified in English-Nadsat. We then employ corpus techniques which demonstrate the high level of consistency that Belmont and Chabrier used in their translation to ensure that the lexical distinctions present in English-Nadsat are largely preserved in the translation. This paper thus demonstrates the value of corpus methodologies in investigating the consistency of translations of creative texts where a third “language” (L3) is present, an approach that is largely lacking in previous work on the translation of this novel into other languages.